Overview and analysis of the polyprotein cleavage sites in the family Potyviridae - Adams, M.J; Antoniw, J.F; Beaudoin, F (Molecular plant pathology, 2005)
SUMMARY The genomes of plant viruses in the family Potyviridae encode large polyproteins that are cut by virus‐encoded proteases into ten mature proteins. Three different types of protease have been identified, each of which cuts at sites with a distinctive sequence pattern. The experimental evidence for this specificity is reviewed and the cleavage site patterns are compiled for all sequenced species within the family. Seven of the nine cleavage sites in each species are cut by the viral NIa‐Pro and patterns around these sites are related where possible to the active site–substrate interactions recently deduced following the resolution of the crystal structure of Tobacco etch virus (TEV) NIa‐Pro (Phan et al., 2002. J. Biol. Chem. 277, 50564–50572). In particular, a revised series of cleavage sites for Sweet potato mild mottle virus (genus Ipomovirus) is proposed with a conserved His at the P1 position. This is supported by homology modelling studies using the TEV structure as a template. The data also provide a standard to correct the annotation of some other published sequences and to help predict these sites in further virus sequences as they become available. Comprehensive data for all sequences of each virus in the family, together with some summaries, have been made available at http://www.rothamsted.bbsrc.ac.uk/ppi/links/pplinks/potycleavage/index.html.